2012
DOI: 10.1186/1749-799x-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical stability of a supra-acetabular pedicle screw Internal Fixation device (INFIX) vs External Fixation and plates for vertically unstable pelvic fractures

Abstract: BackgroundWe have recently developed a subcutaneous anterior pelvic fixation technique (INFIX). This internal fixator permits patients to sit, roll over in bed and lie on their sides without the cumbersome external appliances or their complications. The purpose of this study was to evaluate the biomechanical stability of this novel supraacetabular pedicle screw internal fixation construct (INFIX) and compare it to standard internal fixation and external fixation techniques in a single stance pelvic fracture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 22 publications
0
78
0
2
Order By: Relevance
“…In addition, there is no standard in biomechanical testing of pelvic ring fractures. The setup and some of the loads applied in this study were chosen similar to those reported in published studies [24,33,39,43]. In addition, a stepwise increase in loads [12,40] was chosen to simulate the cyclic loading environment resulting from different levels of weightbearing (toe-touch, walking with a walker, full weightbearing) because they would be expected in the heterogeneous elderly population with fragility fractures of the pelvis with very different levels of balance, compliance, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no standard in biomechanical testing of pelvic ring fractures. The setup and some of the loads applied in this study were chosen similar to those reported in published studies [24,33,39,43]. In addition, a stepwise increase in loads [12,40] was chosen to simulate the cyclic loading environment resulting from different levels of weightbearing (toe-touch, walking with a walker, full weightbearing) because they would be expected in the heterogeneous elderly population with fragility fractures of the pelvis with very different levels of balance, compliance, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…A second procedure is required for the removal of the implant at a minimum of 3-month time frame, which is most commonly described in the literature [5, 8]. Biomechanical studies have shown that the minimally invasive INFIX has superior stability to external fixation, due to the shorter lever arm of the construct [9]. However, compared with internal fixation, it has less stability and stiffness [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have shown that the minimally invasive INFIX has superior stability to external fixation, due to the shorter lever arm of the construct [9]. However, compared with internal fixation, it has less stability and stiffness [9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method would also be an option where further abdominal surgeries are expected avoiding a potentially unstable "RHOMBOID" configuration. There is some evidence that such a device would be at least as stable as an external fixator [27].…”
Section: Discussionmentioning
confidence: 99%